Information Disclosure as a Matching Mechanism: Theory and Evidence from a Field Experiment - Tadelis, Steven; Zettelmeyer, Florian (American Economic Review, 2015)
Market outcomes depend on the quality of information available to its participants. We measure the effect of information disclosure on market outcomes using a large-scale field experiment that randomly discloses quality information in wholesale automobile auctions. We argue that buyers in this market are horizontally differentiated across cars that are vertically ranked by quality. This implies that information disclosure helps match heterogeneous buyers to cars of varying quality, causing both good and bad news to increase competition and revenues. The data confirm these hypotheses. These findings have implications for the design of other markets, including e-commerce, procurement auctions, and labor markets. (JEL C93, D44, D82, L15)